The Isolation, Identification, and Insecticidal Activities of Indigenous Entomopathogenic Nematodes (Steinernema carpocapsae) and Their Symbiotic Bacteria (Xenorhabdus nematophila) against the Larvae of Pieris brassicae - Preety Tomar; Neelam Thakur; Avtar Kaur Sidhu; Boni Amin Laskar; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd_Allah (Horticulturae, 2023)
The cabbage butterfly, Pieris brassicae Linnaeus (Lepidoptera: Pieridae), is an oligophagous and invasive insect pest of various economically important cole crops. Recently, there have been reports about an increase in the incidence and damaging activities of cabbage butterflies, signifying that the existing control methods fail to meet the grower’s expectations. Entomopathogenic nematodes (EPNs) and their endosymbiotic bacteria have immense potential for the control of a wide range of insect pests. In this investigation, the EPN species Steinernema carpocapsae and its associated bacterial species, Xenorhabdus nematophila, were isolated and identified through morphological and molecular techniques. The laboratory bioassay experiment was performed using S. carpocapsae and X. nematophila against the 3rd instar larvae of P. brassicae (25 ± 1 °C; RH = 60%). The efficacy of EPN suspension (30, 60, 90, 120, 150 IJs/mL) and bacterial suspension (1 × 104, 2 × 104, 3 × 104, 4 × 104, and 5 × 104 CFU/mL) via contact and oral routes showed significant mortality among the larvae. Surprisingly, 100% insect mortality within 48 h was recorded in the bacterial inoculum 5 × 104 CFU/mL. However, in the case of EPNs (S. carpocapsae), 150 IJs/mL caused the highest, 92%, larval mortality rate after 96 h. The results signify that both indigenous EPNs and their associated bacteria can provide efficient control against P. brassicae larvae and could effectively contribute to IPM programs. However, further analyses are required to authenticate their effectiveness in field conditions.